PREJUDICE AND RELIGIOUS CONFLICT IN MULTICULTURAL SOCIETY - Eri Nur Shofi'i (PROCEEDING AL GHAZALI International Conference, 2023)
The Indonesian nation is a multicultural nation with diversity found in several aspects of life, such as ethnicity, culture, religion, social status and so on. Basically, multiculturalism not only has potential for the development of the Indonesian nation, but on the other hand it can also bring about horizontal conflicts that must be resolved wisely. Conflicts that occur in multicultural societies must be processed so that they can lead to a dynamic process of change in a constructive and positive direction, rather than leading to destructive actions. The resolution of a conflict will generally depend heavily on internal and external factors. Internal factors are how the conflicting parties respond to the conflict they face, while external factors are how outside parties play a role in handling the conflict. Therefore, it is important to create a plan and steps for conflict management in the form of peace building, so that the dynamic process of multicultural society is maintained well.